2003
DOI: 10.1103/physrevlett.91.223901
|View full text |Cite
|
Sign up to set email alerts
|

Strong Spatiotemporal Localization in a Silica Nonlinear Waveguide Array

Abstract: We investigate the propagation of short, intense laser pulses in arrays of coupled silica waveguides, in the anomalous dispersion regime. The nonlinearity induces trapping of the pulse in a single waveguide, over a wide range of input parameters. A sharp transition is observed for single waveguide excitation, from strong diffraction at low powers to strong localization at high powers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
46
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(47 citation statements)
references
References 12 publications
1
46
0
Order By: Relevance
“…This allows us to employ perturbation methods and to compute the soliton profile and related quantities (soliton power, perturbed zero eigenvalues λ (N ) 0,j , see below) asymptotically. In nonlinear optics, typical lattice periods are of the order of several microns and typical input beam sizes are not smaller than this period [6,22,25,32,33]. Hence, typically, the input beam sizes are not small compared with the lattice period.…”
Section: Introductionmentioning
confidence: 99%
“…This allows us to employ perturbation methods and to compute the soliton profile and related quantities (soliton power, perturbed zero eigenvalues λ (N ) 0,j , see below) asymptotically. In nonlinear optics, typical lattice periods are of the order of several microns and typical input beam sizes are not smaller than this period [6,22,25,32,33]. Hence, typically, the input beam sizes are not small compared with the lattice period.…”
Section: Introductionmentioning
confidence: 99%
“…It is also relevant to mention that experimental observation of spatiotemporal self-focusing of light in silica waveguide arrays, in the region of anomalous group-velocity dispersion (GVD), was reported in Ref. [14].…”
Section: Introductionmentioning
confidence: 99%
“…The main reason for their appli− cation is the well−established fabrication process which allows for structural regularity to be easily accomplished. Moreover, relatively long propagation distance (when com− pared to few−mm−long arrays and lattices etched in semi− conductors [22][23] or optically−induced in photorefractives [24][25], respectively, and few−cm−long waveguide arrays in silica [21]) that can be achieved in PCF−based discrete systems allows for a wide range of different (discrete) prop− agation effects to be obtained, including spatio−temporal nonlinear ones. Photonic crystal fibres are ideally suited to be combined with liquid media, while their hollow sections can be easily infiltrated with use of capillary forces or high pressure.…”
Section: Introductionmentioning
confidence: 99%
“…It can be shown that in such photonic struc− tures, output intensity profile strongly depends on optical and geometrical parameters of the system (including wave− length, beam−size, lattice arrangement and index contrast). Discrete photonic systems (of different dimensionality) have been practically achieved in various materials, includ− ing (fused) silica [19][20][21], semiconductors [22][23], photo− refractives [24][25], polymers [26], ferroelectrics [27], and liquid crystals [12,28], thus giving a rise to many new phe− nomena which are not accessible in homogeneous bulk media. An overview of theoretical and experimental devel− opments in the area of discrete light propagation in linear and nonlinear photonics lattices can be found in Refs.…”
Section: Introductionmentioning
confidence: 99%